Use of metribuzin, associated with different foliar fertilizers, on carrot crops - Soares da Silva, Gustavo; Oliveira Pessoa, Gabriella Daier; Valadão Silva, Daniel; Ramos de Campos, Eduardo; Rodrigues dos Reis, Marcelo; Alberto da Silva, Antonio (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
This study aimed to evaluate the use of different foliar fertilizers, associated or not associated with metribuzin, in terms of carrot yield. The experiments were carried out over two crop years with treatments in a 2×4 factorial scheme. The first factor was the absence or presence of metribuzin (0 and 288 g ha-1 a.i.) and the second factor was the foliar fertilizers: FertiG, FertiB, sucrose and no application. In crop year 1, the commercial yield increased with FertiG with metribuzin, and the forked/total discard ratio decreased when the foliar fertilizers were applied together with metribuzin. The isolated metribuzin decreased the total yield and the commercial/total yield ratio in crop year 1; however, the stress was attenuated when FertiG was applied. In crop year 2, the metribuzin, isolated or associated with FertiG, increased the commercial yield. The FertiB decreased the forked/total discard ratio. The metribuzin, isolated or associated with FertiG, and FertiB obtained similar results for the commercial/total yield ratio in crop year 2. FertiG satisfactorily attenuated the stress caused by metribuzin in the carrot plants, with a positive effect on the commercial yield of the carrot crop.